Amalgam Phase-Down Part 1: UK-Based Posterior Restorative Material and Technique Use. (January 2022) - Bailey, O.; Vernazza, C.R.; Stone, S.; Ternent, L.; Roche, A.-G.; Lynch, C.
Introduction: A European Union amalgam phase-down has recently been implemented. Publicly funded health care predominates in the United Kingdom with the system favoring amalgam use. The current use of amalgam and its alternatives has not been fully investigated in the United Kingdom. Objectives: The study aimed to identify direct posterior restorative techniques, material use, and reported postoperative complication incidence experienced by primary care clinicians and differences between clinician groups. Methods: A cross-sectional survey was distributed to primary care clinicians through British dentist and therapist associations (11, 092 invitations). The questionnaire sought information on current provision of direct posterior restorations and perceived issues with the different materials. Descriptive statistical and hypothesis testing was performed. Results: Dentists' response rate was 14% and therapists' estimated minimum response rate was 6% (total N = 1, 513). The most commonly used restorative material was amalgam in molar teeth and composite in premolars. When placing a direct posterior mesio-occluso-distal restoration, clinicians booked on average 45% more time and charged 45% more when placing composite compared to amalgam ( P < 0.0001). The reported incidences of food packing and sensitivity following the placement of direct restorations were much higher with composite than amalgam ( P < 0.0001). Widely recommended techniques, such as sectional metal matrix use for posterior composites, were associated with reduced food packing ( P < 0.0001) but increased time booked ( P = 0.002). Conclusion: Amalgam use is currently high in the publicly funded sector of UK primary care. Composite is the most used alternative, but it takes longer to place and is more costly. Composite also has a higher reported incidence of postoperative complications than amalgam, but time-consuming techniques, such as sectional matrix use, can mitigate against food packing, but their use is low. Therefore, major changes in health service structure and funding and posterior composite education are required in the United Kingdom and other countries where amalgam use is prevalent, as the amalgam phase-down continues. Knowledge Transfer Statement: This study presents data on the current provision of amalgam for posterior tooth restoration and its directly placed alternatives by primary care clinicians in the United Kingdom, where publicly funded health care with copayment provision predominates. The information is important to manage and plan the UK phase-down and proposed phase-out of amalgam and will be of interest to other, primarily developing countries where amalgam provision predominates in understanding some of the challenges faced.